The Victim's Best Interest Principle in Islamic Law: An Examination of the Substance of Sexual Violence in Muslim Majority Countries in the Contemporary Era - Elfa Murdiana; Nunung Rodliyah; Rudi Natamiharja; M. Nur Fathoni; Gautam Kumar Jha (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This article examines the extent to which the principle of the best interests of victims is accommodated within the legal frameworks for protecting victims of sexual violence in Muslim-majority countries. It critically explores the normative and practical gap between Islamic legal principles—particularly the protection of life (ḥifẓ al-nafs) and honor (ḥifẓ al-‘irḍ)—and the operation of positive law in Indonesia, Malaysia, and Egypt. The central questions addressed are how victim protection is conceptualized and regulated within the legal systems of these three countries, and whether the best interests of victims have been established as the primary normative and policy orientation. This study employs a normative juridical method, utilizing comparative and conceptual approaches, and analyzes statutory regulations, legal doctrines, court decisions, and relevant academic literature. The findings reveal that, despite recent legal reforms, existing regulatory frameworks remain predominantly perpetrator-oriented. Victim protection is often treated as supplementary rather than foundational, resulting in limited access to justice, insufficient recovery mechanisms, and weak institutional responsiveness to victims’ needs. Building on a Maqāṣid al-Sharī‘ah perspective, this article proposes a legal reconstruction that re-centers the protection of victims as a core objective of Islamic and national legal systems. It argues that the principle of the best interests of victims is not only compatible with Islamic law but is inherently embedded within its ethical and purposive framework. Accordingly, the study recommends strengthening substantive legal norms, procedural safeguards, institutional coordination, and legal culture to ensure holistic and equitable victim protection. The academic contribution of this article lies in its integration of Maqāṣid al-Sharī‘ah with comparative victimology, offering a normative framework that bridges Islamic legal theory and contemporary human rights discourse. It advances the discussion on victim-centered justice by providing a contextualized Islamic legal justification for prioritizing victims’ interests within modern legal systems.